ANALYSIS OF WILLIAM SHAKESPEARE`S “ROMEO AND JULIET” AND GANJAVI`S “LAYLA VA MAJNUN” - Umaralieva Munojat Mashrabovna; Obidova Shoxistaxon Nuridinjon qizi (Лучшие интеллектуальные исследования, 2024)
Abstract: This article offers a comparative literary analysis of William Shakespeare`s “Romeo and Juliet” and Ganjavi`s Layla and Majnun” two influential works of world literature. The analysis examines the thematic, allegorical, and cultural dimensions of these texts, highlighting their profound resonance and universal significance across diverse cultural and linguistic contexts.